PRESERVING LAKE POSO THROUGH THE INTEGRATED AND COMPREHENSIVE LEGAL POLICIES - Lembang Palipadang; Sulbadana Sulbadana; Andi Intan Purnamasari; Supriyadi Supriyadi (Cepalo, 2025)
Lake Poso, Indonesia's third-largest lake, faces severe ecological threats that endanger its biodiversity and the livelihoods of local communities. Despite its ecological significance, legal and policy responses remain fragmented, hindering effective conservation. This research employs a normative research method, integrating doctrinal and statutory approaches with qualitative analysis of relevant regulations and scientific literature. Findings highlight critical challenges, including endemic species decline, water quality degradation, climate change impacts, and socio-economic pressures from fisheries decline and unregulated tourism. Governance fragmentation emerges as a central issue, with national laws lacking ecosystem-specific provisions and regional regulations suffering from weak enforcement, limited institutional capacity, and inadequate funding. Drawing on successful conservation models from other Indonesian lakes, this research proposes a framework for integrated legal policies. Key recommendations include watershed management, sustainable fisheries practices, targeted pollution control, climate adaptation measures, and community-based conservation incorporating traditional ecological knowledge. By addressing regulatory gaps and enhancing policy coherence, this research provides a roadmap for Lake Poso’s long-term preservation and sustainable development.